A supplementary description of Brisaster iheringi (Spatangoida: Schizasteridae) from the Miocene of Patagonia Argentina - Martínez, Sergio (2017)
Neogene Argentinean echinoids are important biostratigraphic tools. New specimens of Schizaster iheringi (de Loriol, 1902) from Early Miocene sedimentites (Chenque Formation, Patagonia, Argentina) allowed us to improve its original description, providing for the first time details of the apical disc and the oral side of  test. The species is included into the genus Brisaster: the first unquestionable documented reference to the taxon from the Neogene of Argentina. All previously reported specimens of this species are evaluated, concluding that the stratigraphic range of the genus Brisaster in Patagonia must be restricted to the Early Miocene. Rev. Biol. Trop. 65(Suppl. 1): S137-S146. Epub 2017 November 01.